Feasibility study of using blockchain to improve transparency and trust in the charity industry - Pahl, Julika (Accounting and Accountability in Africa, 2021)
In 2012, the UN Secretary stated that corruption prevented 30 percent of all development assistance from reaching its destination (UNSG, 2012). This thesis discusses the importance of trust and transparency in the charity sector, and how technology, specifically blockchain, could address these two factors. This paper aims to demonstrate this by developing a minimum viable product on the Ethereum blockchain, called the LoveEconomy, for a local South African non-profit organization, the Secret Love Project. The LoveEconomy is designed as a circular economy, whereby local businesses and users of the platform benefit from each other, whilst also supporting the charity, which takes care of homeless people in Cape Town. Blockchain has many features that could potentially transform charitable giving and aid distribution by enhancing transparency, reducing costs through disintermediation, and enabling new mechanisms for monitoring and tracking charities' impact. Trust and transparency are closely linked in the charity industry, as transparency about the distribution of the funds and the end impact are critical for the trust of the public (Populus and Charity Commission For England & Wales, 2018).